THE EFFECTIVENESS OF ONLINE BASED LEARNING DURING THE COVID-19 PANDEMIC AT PRIVATE SCHOOL IN BOGOR - Arief Rachman Badrudin; Muhammad Hidayat Ginanjar; Wartono Wartono (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
The research is to find out the effectiveness of online distance learning at an elementary school program in Bogor. This study's approach was descriptive qualitative on survey research to 621 respondents, including the headmaster, teacher, and other stakeholders. The results showed that online distance learning at elementary was active. Therefore, the next evaluation from the headmaster, teacher, and local government supports increasing quality. Also, for improving students, competence should have good cooperation from the headmaster, teacher, and parents in service all the equipment online distance learning.